The Archive of University Science as the Core of Research Education in Russia: the Motivational Potential of Social Software - I. O. Shchedrina; B. I. Pruzhinin; T. G. Shchedrina (Высшее образование в России)
Social Software as a special kind of organization of goal-oriented joint activity is considered in the present article in the context of cultural-historical epistemology, which is based on the understanding of knowledge as a sign-semiotic, historical phenomenon. This approach, according  to  the  authors,  makes  it  possible  to  reveal  in  a  new  way  the  educational  and  pedagogical  potential  of  social  software,  which  today  attracts  the  attention,  first  of  all,  of  sociologists,  political scientists, and economists, who only partially touch upon its cognitive parameters. Meanwhile, appeal to the epistemological dimension of social software allows us to emphasize characteristics that significantly expand the scope of its application, and in particular, the characteristics that open up an additional opportunity to quite effectively motivate students for self-education, for an inherently creative understanding of knowledge as a sociocultural value. The “motivational” potential of social software today is acquiring a particularly important role in the educational structures of “research education”. In such structures, step-by-step software opens up for the student, on the one hand, a sequence of operations that lead research to knowledge as the goal of education, and on the other hand, it dramatically changes in the eyes of students the process of assimilation of information determined by the curriculum, since it involves participation in its “creation”. At the same time, the presence of a social dimension in the software gives cultural and historical meaning to the sequence of students’ efforts, which opens up additional opportunities for motivating their activity through an appeal to the cultural and historical status of the scientific activity within which this knowledge was firstly created. The article demonstrates the experience of implementing one of these opportunities to additionally stimulate the attitude towards self-education through the introduction of philosophy faculties students to archival research of university science in Russia.